Two-Sided Uncertainty and "Up-or-Out" Contracts - Kahn, Charles; Huberman, Gur (Journal of Labor Economics, 1988)
A bilateral moral-hazard problem provides a rationale for "up-or-out" employment contracts. The employer sets a wage higher than opportunity cost to induce the worker to invest in firm-specific capital. If the individual does not make the grade, it is in the firm's interest ex post to fire him. Had the initial arrangement not included provisions for firing individuals, the firm would underreport the value of the employee, wrecking the incentive scheme. The basic model permits both firm and worker to be risk neutral. Therefore, it admits a straightforward multiperiod extension, which we also investigate.